mʾfyynym rṭṿryym ṿsgnṿnyym shl sfrṿt frshnṿt htlmṿd vdṿrṿt hʾḥrṿnym hdgmh mʾskhṿlt sṿlṿvyyts'yḳ / Rhetorical and Stylistic Characteristics of Talmudic Exegesis Literature The Case of the Soloveitchik School - Ḥarlap, Lubah Raḥel (Hebrew Union College annual, 2009)
This article touches on one specific genre of rabbinic literature: the Talmud exegesis from the school of Rav Hayyim Soloveitchik and his successors, also called: the "Brisk school." Our objective is to examine this genre with a rhetorical-stylistic approach, using modern tools of textual linguistics analysis. The article targets two distinctive topics: 1. a characterization of the unique rhetorical model of the "Brisk school" texts, 2. a description of some discursive elements within the text, and its various implications. We used a combined rhetorical model to map three "case study" texts taken from "Soloveitchik School" writers. One can see that at the core of every exegetical issue lies a yesod (the basic element), which always consists of two dinim — two different halakhic concepts. The authors of these texts attempt to reconcile every possible proponent with its opponent until their thesis is proven. As to the discursive aspect of our research, despite the high frequency of connectives, we find that the beginnings and endings of citations are, to a large extent, inexplicit. This, in addition to other indicators, leads us to the conclusion that these texts are syntactically ambiguous. It seems that this tendency expresses the authors' intention to let their studies be approachable only to those who, according to their standards, qualify as "specialist readers."